ABO blood type, smoking status, other risk factors and prognosis of pancreatic ductal adenocarcinoma. Issue 14 (April 2020) - Li, Shuang-Shuang; Zhou, Cong-Ya; Liao, Rong; Xiong, Lai; Weng, Ning-Na; Zhao, Ya-Qin; Mason, Clifford; Gou, Hong-Feng; Yi, Cheng; Zhu, Qing
Abstract : Abstract: The aim of this observational study was to test whether ABO blood type was a prognostic factor for pancreatic ductal adenocarcinoma (PDAC) patients and whether other risk factors could influence pancreatic cancer patients' survival. This study included 610 patients who were diagnosed as pancreatic cancer and had undergone radical surgery. Patients' characteristics included age, gender, tumor stage, tumor grade, adenosquamous carcinoma (ASC) status, preoperative serum carbohydrate antigen 19-9 (CA19-9) levels, preoperative serum carcinoembryonic antigen (CEA) levels, ABO blood type, smoking status, and drinking status were analyzed in this study. Cox proportional hazards regression model and Kaplan–Meier method were used to evaluate the role of prognostic factors. For pancreatic cancer patients undergoing radical surgery, the overall survival was worse for ASC patients than PDAC patients (Log-rank = 11.315, P  < .001). Compared with ASC patients (Log-rank < 0.001, P  = .996), PDAC patients can benefit from chemotherapy (Log-rank = 17.665, P  < .001). For PDAC patients, O blood type had better overall survival than non-O blood type (Log-rank = 4.153, P  = .042). Moreover, the group with higher serum levels of CA19-9 had poor prognosis compared to another group with low serum CA19-9 (Log-rank = 4.122, P  = .042). Higher CEA levels indicated poor prognosis (Log-rank = 13.618, P  < .001). In conclusion, ASC status was associated with overall survival of pancreatic cancer patients and cannot benefit from postoperative chemotherapy. Non-O blood type was a prognostic factor for PDAC patients. Abstract : Supplemental Digital Content is available in the text